“Preferencia de archaeoprepona demophon muson (fruhstorfer, 1995), nymphalidae: charaxinae), por diferentes sustratos de alimentación en condiciones de cautiverio en la microcuenca del rio shilcayo-Tarapoto.” - Gonzáles Alegria, Raúl (2006)
At the present time the upbringing of butterflies has beco me a productive <and-~·~,/ profitable commercial activity. Organisms exist in the world that they market dissected butterflies and live, mainly in their state pupal, having as market objective collectors at world level that they go from specialized investigators to simple curious or lovers of the nature. The objective was to determine the biological cycle and to determine host potentials with tests of selectivity of Archaeoprepona demophon musan (Fruhstorfer, 1905), (Nymphalidae.- Charaxinae), under lower captivity conditions in the microcuenca of the River Shilcayo-Tarapoto. For the selectivity tests was used Rollinia, Aniba, Annona and Citrus leaves, they were conditioned respectively in badges petris clipped 2.25 cm2, the leaves were of soft texture to facilitate the feeding of the first stadiums, being renovated in daily form. The duration of the biological cycle was carried out with leaves of the goods Rollinia sp., and Aniba sp., being these those but favorite (112 and 60 individuals for treatment respectively), it fed to each larva with 9 cm2 leaf until the fourth stadium and 18 cm2 when arriving at the fifth larval stadium. The evaluations were carried out in daily form, for the gathering of the postures, selectivity tests and biological cycle. The work was developmented under conditions of a temperature maximum average of 28,0 ºC, temperature mínimum average of 24, 1 and a humidity relative maxim average of 85,3% and mínimum of 70,0%, the recovered material was identified by the Dr. Gerardo Lamas Müller, boss of the department of Entomology of the Museum of Natural History of the National University Mayor, San Marcos. The results show us that for the rehearsal it has more than enough favorite leaves initially a bigger preference it exists for leaves of the gender Aniba, with 35,29% of acceptance followed by Rollinia, with 23,53%, Citrus, with 21,27 and finally for Annona, with 19,91 % of acceptance, the test of sqLiared Ji shows LIS that eqLiality doesn't exist among the treatments, having a probability of obtaining a deviation at least as big as the observed one by chance of OA5%. For the rehearsal it has more than enoLigh favorite leaves finally for their establishment it shows that a bigger preference exists for leaves of the gender Rollinia, with 35,91 % of acceptance followed by Aniba, with 26,82%, Annona, with 22,27% and finally for Citrus, with 15,00% of acceptance. The test of sqLiared Ji shows LIS that eqLiality doesn't exist among the treatments, having a probability of obtaining a deviation at least as big as the observed one by chance of 0,02%. Far the dLiration of the biological cycle, with the treatment leaves of the gender Rol/inia, was of 108,22 days, while the treatment with leaves of the gender Aniba, was of 94,27 days. The correlation stLidy indicates LIS that a clear effect of the environment existed in the development of the individLials, since this factor exercises similar effect in both treatments.